The researh for study relationship between phytoplankton abundance and environment parameters and determining contribuion each environment parameters on phytoplankton abundance discrimination had been conducted in 2005 in bagan rambo fishing ground at coastal water Barru Regency, Makassar Strait. Environment parameters and phytoplankton abundance data collection were conducted on May (6 stations), June, July, September, October and November (9 stations). Spatio-temporal distribution of environ - Muh. Hatta; Richardus F Kaswadji; Mulia Purba; Daniel R. Monintja (Forum Pasca Sarjana, 2010)
The researh for study relationship between phytoplankton abundance and environment parameters and determining contribuion each environment parameters on phytoplankton abundance discrimination had been conducted in 2005 in bagan rambo fishing ground at coastal water Barru Regency, Makassar Strait. Environment parameters and phytoplankton abundance data collection were conducted on May (6 stations), June, July, September, October and November (9 stations). Spatio-temporal distribution of environment parameters probably ralate to fresh water loading to stations inshore. Phytoplankton abundance found in this research ranged from 431 to 5438 cels/liter. Phytoplankton population dominated by diatom i.e: Bacteriatrum, Biddulphia, Chaetoceros, Coscinodiscus, Ditylum, Eucampia, Melosira, Navicula, Nitzschia, Rhizosolenia, Skeletonema, Thalassionema, Thalassiosira, dan Thalassiothrix. Regression analysis result show significantly positive linear correlation between phytoplankton abundance with temperature and phosphate concentration, but low correlation coefficient R = 0,4366 (R2 = 0,1906). Discriminant analysis result show that high average of phytoplankton abundance occured when high temperature and nitrat concentration, and moderate salinity, pH and phosphate concentration. Phosphate concentration have higher contribution on discriminating phytoplankton abundance. The contribution of nitrate and silicat concentration and pH are low. Key words: phytoplankton, phytoplankton abundance, diatom, discriminant analysis, environment parameters